Pengenalan Immersive Marketing Dan Penyesuaian Pricing Dengan Pelaku Usaha Bumdes Kesari Amertha Sari - Putri, Sukmasari Triana Gita (Dharma: Jurnal Pengabdian Masyarakat, 2024)
This community service was carried out to introduce the concept of marketing and financing calculations at the Kesari Amertha Sari Village-Owned Enterprise which was carried out with the collaboration of Warmadewa University lecturers and students. The implementation of the service was carried out in Singapadu Tengah Village, Sukawati District, Gianyar Regency, Bali Province. Service activities are carried out using observation and interview methods conducted to BumDes managers and Pokdarwis groups in Singapadu Tengah. The results of observations and interviews became the basis for implementing the service program by action research group methods. It is known that BumDes and Pokdarwis Singapadu Tengah are currently experiencing obstacles to revive through tourist villages. As a result, representatives of Bumdes and Sadar Wisata groups understand the importance of marketing that is done digitally but still provides real time services and opportunities for managing tourist village pricing to be carried out, after socialization related to immersive marketing and pricing strategy guidelines, especially in tax adjustments. The evaluation of the service program shows positive results in supporting the marketing and management of tourist villages in Singapadu Tengah. This service activity has successfully achieved its goal of introducing the knowledge and skills of Bumdes and Pokdarwis in the management of tourist village.